Visible light communication cooperative system to support indoor guidance services - Vieira, Manuela (2022)
To support people’s wayfinding activities we propose a Visible Light Communication (VLC) cooperative system that supports guidance services and uses an edge/fog based architecture for wayfinding services. A mesh cellular hybrid structure is proposed. The dynamic navigation system is composed of several transmitters (ceiling luminaries) which send the map information and path messages required to wayfinding. The luminaires are equipped with one of two types of nodes: a “mesh” controller that connects with other nodes in its vicinity and can forward messages to other devices in the mesh, effectively acting like routers nodes in the network and a “mesh/cellular” hybrid controller, that is also equipped with a modem providing IP base connectivity to the central manager services. These nodes acts as border router and can be used for edge computing. Mobile optical receivers, using joint transmission, collect the data at high frame rates, extracts theirs location to perform positioning and, concomitantly, the transmitted data from each transmitter. Each luminaire, through VLC, reports its geographic position and specific information to the users, making it available for whatever use. Bidirectional communication is implemented and the best route to navigate through venue calculated. The results show that the system makes possible not only the self-localization, but also to infer the travel direction and to interact with information received optimizing the route towards a static or dynamic destination.